The man-lovers : a searching new study of those "odd" men who can feel sex desire only for other men - Kuster, Earl (New York : New Library Book, 1967)
Fonds Suzan Daniel (FSD)
Fonds Suzan Daniel (FSD)F/02/016 Archief Roger Vertongen
Engels
Monografie